Cross-cultural adjustment on expatriates’ job performance in Celcom Axiata Berhad / Raja Noornadia Raja Kamal - Raja Kamal, Raja Noornadia (2015)
Celcom Axiata Berhad is among the largest Telecommunication Company in Malaysia. In order to maintain its level of competitiveness in the industry, they would hire professional manager or expatriates from different country to achieve that mission. The purpose of this research is to study the cross-cultural adjustment on expatriates' job performance in Celcom Axiata Berhad. Through this research, researcher wants to identify the relationship between cross-cultural training and expatriates’ job performance, the relationship between organizational and family support and expatriates’ job performance, the relationship between personality and expatriates’ job performance and lastly the relationship between emotional intelligence and expatriates’ job performance. Furthermore, researcher also wants to identify which of the factors to be the main key determinant that affects expatriates’ job performance in Celcom Axiata Berhad. For this study, researcher is using census sampling technique, where 35 questionnaire were distributed to all the respondents who are the expatriates working in Celcom Axiata Berhad. Apart from that, researcher use primary and secondary data for supporting the sampling technique. The findings are interpreted through Frequency, Descriptive analysis, Reliability analysis, Pearson correlation analysis and Correlation analysis using Statistical Package for Social Sciences (SPSS) 21.0. The respondents were being approach at Menara Celcom Axiata Berhad itself. The finding indicates that both dependent and independent variables has a relationship and they are significant.